(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
The present study was designed to evaluate the effect of different hydrophobic materials and their loading level on the release profile of etoricoxib, a model lipophilic drug, from matrix systems. Matrix tablets of the drug were prepared using compritol, precirol, glyceryl monostearate, cetostearyl alcohol and eudragit as release retarding agents by direct compression process. The resulting monolithic tablets were found to have optimum hardness, uniform thickness, high content uniformity and low friability. All tablet formulations yielded quality matrix preparations with satisfactory tableting properties. Increasing the concentration of hydrophobic materials significantly decreased the friability (from 2.73 to 0.46 in case of eudragit) and subsequently increased the tensile strength (0.237 to 0.908 in case of eudragit) of the formulated tablets. At higher hydrophobic level (50% of the matrix), the rate and extent of drug release was significantly reduced due to increased tortuosity and reduced porosity of the matrix. Compritol imparted the strongest retardation of drug release amongst the selected lipid based materials. In vitro drug dissolution and mathematical modeling were used to characterize drug release rate and extent. The release kinetics was found to be governed by the type and content of hydrophobic materials in the matrix. Numerical fits indicate that the Higuchi square root of time model (TEUD I, TEUD II, TCSA I and TCSA II), Hixson-Crowell cube root model (TGMS I, TCOM I and TPRE I) and Korsemeyer Peppas model (TGMS II, TCOM II and TPRE II) were the most appropriate one for describing the release profile of etoricoxib from hydrophobic matrices. Mathematical modeling indicated that the drug release followed a combination of diffusion and erosion mechanism.